Assessment for education standards, judgement and moderation - Klenowski, Val 1952-; Wyatt-Smith, Claire (SAGE, 2014)
Do you need a practical guide to assessment, curriculum and policy? Are you also looking for a book that is firmly grounded in theory and professional practice? This book makes assessment processes transparent for practitioners, and shows how assessment should align with curriculum and teaching for success in education. The book will show you how practitioner use of achievement standards can improve learning, equity, social justice and accountability. Inside this book, you will learn about: - quality assessment and judgment practice - relationships across curriculum, assessment, teaching and learning - front-ending assessment based on the learner's needs - practitioner judgment approaches and standards - the conditions under which teacher assessment can be valid - principles derived from research of social moderation practices